Populism and its Horizon of Expectations: Threat to, Critique of, or Remedy for Liberal Democracy - Chakravarty, Udeepta (Journal of Political Sociology, 2025)
Despite the intellectual mire around definitions, all theories of populism implicitly or explicitly make claims about its (negative or positive) consequences, specifically, its consequences for liberal democracy. All theories of populism can be classified as either articulating a threat to, a critique of, or a remedy for liberal democracy. This article will lay out the overall terrain of normative disputes within the field of populism studies and critically evaluate these positions. The ambition is to make clear that theoretical and definitional debates are not devoid of actual political and normative considerations. In fact, Populism as a political concept attains normative significance within a liberal democratic discourse and, as this paper will demonstrate, different theorists, depending on their commitments to and theorizations of liberal democratic politics, furnish different accounts of the reality populism produces—generating a contested horizon of expectations.